Effects of multiple parameters on static electrification and breakdown strength of transformer oil. Issue 6 (1st September 2016) - Liu, Daosheng; Du, Boxue; Liu, Feifei; Wang, Shihui
Abstract : Forced convection of insulation oil is the main heat transfer mode in large‐power and ultra‐high‐voltage (UHV) transformers. The electrification hazard caused by physicochemical phenomena between mineral oil and pressboard has been suspected to be responsible for several failures. The electrification measurement was carried out in an oil flow system. The influences of oil temperature, flow velocity, time and applied electric field of fresh and dry transformer oil have been investigated by a measurement system. The experimental results from the oil flow system show that the streaming current increases with the increase of the temperature when the temperature is below 50°C, while it reverses when the temperature is above 50°C. The streaming current increases with the increase of AC and DC electric fields under the different flow velocities, but the streaming current polarity reverses with DC electric field polarity under the 6.9 m/s flow velocity. The electrification phenomenon can lead to reduction of the breakdown strength of the oil. It is concluded that some effective measures should be taken to restrain the possible harm caused by the streaming electrification in UHV converter transformer.